Efficient Sunlight Harvesting by A4 β-Pyrrolic Substituted ZnII Porphyrins: A Mini-Review - Di Carlo, Gabriele; Orbelli Biroli, Alessio; Pizzotti, Maddalena; Tessore, Francesca (Frontiers in Chemistry, 2019)
Dye-Sensitized Solar Cells (DSSCs) are a highly promising alternative to conventional photovoltaic silicon-based devices, due to the potential low cost and the interesting conversion efficiencies. A key-role is played by the dye, and porphyrin sensitizers have drawn great interest because of their excellent light-harvesting properties mimicking photosynthesis. Indeed porphyrins are characterized by strong electronic absorption bands in the visible region up to the near infrared and by long-lived * singlet excited states. Moreover the presence of four meso and eight -pyrrolic positions allows a fine tuning of their photoelectrochemical properties through structural modification. Trans-A2BC push–pull ZnII porphyrins, characterized by a strong and directional electron excitation process along the push–pull system, have been extensively investigated. On the other hand, A4 pyrrolic substituted tetraaryl ZnII porphyrins, which incorporate a tetraaryl porphyrinic core as a starting material, have received lower attention, even if they are synthetically more attractive and show several advantages such as the more sterically hindered architecture and the enhanced solubility in most common organic solvents. The present contribution intends to review the most prominent A4 -substituted ZnII porphyrins reported in the literature so far for application in DSSCs, focusing on the strategies employed to enhance the light harvesting capability of the dye and on a comparison with meso-substituted analogues.